2006
DOI: 10.1007/s00467-006-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemic–hypertensive syndrome in a 15-month-old child with renal artery stenosis

Abstract: In this report we present the case of a 15-month-old girl with hyponatraemic-hypertensive syndrome (HHS) caused by stenosis of the left renal artery. On sonographic examination the contralateral non-stenotic kidney appeared enlarged and with cortical hyperechogenicity mimicking a parenchymal lesion. After successful percutaneous transluminal angioplasty, when the girl became normotensive, her serum electrolyte and acid-base balance became normal within a few days. The contralateral non-stenotic kidney hyperech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 20 publications
4
21
1
Order By: Relevance
“…In another study, proteinuria was correlated with complete renal artery occlusion [9]. Although most case reports presenting massive proteinuria and RAS are in elderly patients [2,[10][11][12][13][14][15][16], there are case reports in infants and young adults, similar to our patients [13,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 87%
“…In another study, proteinuria was correlated with complete renal artery occlusion [9]. Although most case reports presenting massive proteinuria and RAS are in elderly patients [2,[10][11][12][13][14][15][16], there are case reports in infants and young adults, similar to our patients [13,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 87%
“…In the study by Agarwal et al [4], HHS was also reported in association with bilateral RAS in some patients. The authors presumed that critical stenosis and intense stimulation of the renin-angiotensin system in one kidney and pressure natriuresis in the contralateral kidney with sub-severe stenosis may be underlying mechanisms [4,8]. However, it is difficult to apply this argument to individuals with bilateral critical RAS or unilateral stenosis of a solitary functioning kidney as was seen in our patient.…”
Section: Discussioncontrasting
confidence: 41%
“…Renovascular hypertension is responsible for 5-25% of cases of secondary hypertension in children, and fibromuscular dysplasia accounts for up to 60% of cases [9,10]. Renal artery stenosis may be due to external compression [5].…”
Section: Discussionmentioning
confidence: 98%
“…Activation of the reninangiotensin system (RAS) causes secondary hyperfiltration, pressure diuresis, and sodium loss from the contralateral, nonstenotic kidney. Renal handling of other solutes is also affected by this hyperfiltration state, as reflected by findings of hypokalemia, alkalosis, hypercalciuria, glycosuria, and proteinuria, sometimes within the nephrotic range [2,4,8,10]. Several authors reported reversible cortical hyperechogenicity of the nonstenotic kidney, probably a consequence of hyperfiltration and tubulointerstitial damage [10,14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation